The Fahmi Qira'atil Qur'an (FQQ) Method: A Historical and Pedagogical Analysis of an Indigenous Indonesian Quranic Learning Approach - Abdul Rosyid; Sirrotul Ilmi Matdoan (SALAM: Jurnal Sosial dan Budaya Syar-i, 2026)
The development of Qur'anic literacy among Indonesian Muslims has long been a central concern of Islamic education, prompting the emergence of various indigenous methods designed to accelerate and simplify the process of learning to read the Holy Qur'an. This study examines the Fahmi Qira'atil Qur'an (FQQ) method, a Qur'anic learning approach developed by Ahmad Bardji Matdoan in Ambon, Maluku, in the late 1970s. Employing a qualitative descriptive methodology with historical and pedagogical analysis, the research investigates the method's origins, characteristics, instructional design, and distinctive features through examination of the primary textbook and supplementary sources. The findings reveal that the FQQ method emerged as a response to the limitations of the Baghdadiyah method, incorporating a unique three-stage hijaiyah letter recognition system organized alphabetically, combined with simultaneous introduction of letter forms in initial, medial, and final positions. The method integrates tahajji (spelling), talaffuzhi (phonetic), and qiyasi (latinization) approaches within a single-volume textbook structured across three instructional levels from beginner to intermediate. Distinctive features include the classification of fourteen challenging letters with Latin equivalents, the use of fourteen reading sign formulas, and specific terminological variations in tajwid concepts compared to other Indonesian methods. The FQQ method has demonstrated significant longevity, spreading from Ambon to the Tual region of Southeast Maluku, where it continues to be utilized in Taman Pengajian Al-Qur'an institutions and government-sponsored literacy programs. This study contributes to the documentation and analysis of Indonesia's diverse Qur'anic pedagogical heritage, highlighting the importance of preserving and studying locally-developed Islamic educational approaches within their sociocultural contexts. Keywords: FQQ Method, Qur'anic Literacy, Islamic Education, Tajwid Pedagogy, Maluku, Indonesian Islam, Baghdadiyah Method